PERLAWANAN PEDAGANG PASCA REVITALISASI STUDI PENELITIAN DI PASAR IR. SOEKARNO, KABUPATEN SUKOHARJO - Anugraheni Titis Aprilianawati; Nunik Retno Herawati; warsito -; wachid abdulrahman (Journal of Politic and Government Studies, 2018)
This research concerns about the merchants’ resistance that happened after the revitalization of Pasar Ir. Soekarno-Sukoharjo which is located at Jalan Jenderal Sudirman no. 53 Sukoharjo Regency. This study becomes the first study of this locus because most of the research on this locus only examines the aspects of revitalization implementation. Resistance aspect becomes an interesting thing to be studied in this research because in revitalization, it tends to prioritize the aspect of the market’s physical improvement. Meanwhile, on the other hand revitalization done gives less attention to social aspects so that a resistance from the traders emerges. Thus, this study is intended to examine further the case related to Merchants’ Resistance During Post Revitalization of Ir. Soekarno Market in Sukoharjo Regency This study is based on the key questions that emphasize its substance of the policy-making actors and actors who reject the research locus. Specifically, to keep this research in the theoretical corridor, the authors conduct the research by referring to the question